Cerebral aspergillosis and cerebral candidiasis; a retrospective analysis of clinicopathologic features in ramathibodi hospital - Noppadol Larbcharoensub (2018)
Objective: Determine and compare the clinicopathological findings of cerebral aspergillosis with cerebral candidiasis. Material and Method: The medical records with cerebral aspergillosis and cerebral candidiasis in Ramathibodi Hospital between January 1997 and December 2008 were analyzed. The criterion for the diagnosis of cerebral aspergillosis and cerebral candidiasis was the evidence of fungal elements from histopathologic section. The age, gender, neurological manifestations, duration of symptom, associated underlying disease, predisposing risk factor, laboratory data, extent of systemic organ involvement and treatment outcome were analyzed. Results: The present study included cerebral aspergillosis (n = 41) and candidiasis (n = 15). There were 23 male and 33 female patients. The mean and median ages at diagnosis were 39.7 and 45 years, respectively (range, 1 month to 87 years). The clinical presentations included alteration of consciousness (69.6%), fever (60.7%), weakness of the extremity (14.3%), cranial nerve palsy (12.5%), headache (12.59%) and seizure (5.4%). One third of the cases had underlying ematologic malignancy. The cerebral aspergillosis and cerebral candidiasis were associated with corticosteroids treatment in 32.1%. The frequent associated sites of fungal infection included the lungs (73.2%), alimentary tract (33.9%) and sinonasal tract (19.6%). Conclusion: A diagnosis of cerebral aspergillosis and cerebral candidiasis requires a high index of suspicion especially in immunocompromised patients who presented with alteration of consciousness, fever, focal neurological deficit, headache, and seizure. The patients with cerebral aspergillosis and cerebral candidiasis manifest with similar clinicopathologic features. However, the sinonasal tract infection and abscess formation are more common in cerebral aspergillosis. Associated alimentary tract infection is commonly seen in cerebral candidiasis.